Rapid phase separation assisted hydrogel evaporator for solar desalination and water environmental purification - Jianbo Zhang; Jinming Yu; Tongyu Zhang; Zhenjie Ma; Yutian Wang; Bo Ge; Hui Zhao; Tonghui Zhang; Guina Ren; Zhaozhu Zhang (Desalination, 2026)

Potent Inhibitory Effects of Lauric Acid and Glycerol Monolaurate Against CyHV ‐2 and the Viral Envelope - Chenwei Yu; Tonghui Xu; Jiahua Zhang; Bingyu Liu; Ye Zhang; Liqun Lu; Dan Xu (Journal of Fish Diseases, 2026)
Lauric Acid (LA) and Glycerol Monolaurate (GML) are naturally present in several plant‐derived oils, particularly coconut and palm kernel oil. These compounds have been widely applied in swine production owing to their proven antiviral activity against Porcine Reproductive and Respiratory Syndrome Virus (PRRSV), Porcine Epidemic Diarrhoea Virus (PEDV), and African Swine Fever Virus (ASFV). In this study, we investigated the potential of LA and GML as antiviral agents against Cyprinid herpesvirus 2 (CyHV‐2), the causative agent of Herpesviral haematopoietic necrosis (HVHN), which poses significant challenges to China's freshwater aquaculture industry, particularly in crucian carp farming. Notably, no commercially available drugs or vaccines are currently approved for CyHV‐2 infection. Our findings demonstrated that LA and GML significantly inhibit CyHV‐2 replication and reduce viral infectivity. Further investigation into the antiviral mechanisms revealed that treatment with LA or GML disrupts the viral envelope structure, alters its physicochemical properties, and compromises virions' stability. Based on these results, we propose that LA and GML are promising natural antiviral agents for the control of CyHV‐2 infection.

PFOS exposure at environmentally relevant concentrations promote papillary thyroid carcinoma progression through PI3K/AKT/mTOR-mediated epithelial-mesenchymal transition - Yaling Yu; Yi Wang; Xuling Su; Zhenzhen Cai; Qianqian Wang; Chenglong Wang; Yiwei Zhao; Tonghui Zhang; Danjie Hu; Zhiyan Liu (Environmental Research, 2026)

Identification, prediction and optimization of conflicts in production-living-ecological space in semi-arid areas based on the perspective of eco-environmental value: a case study of Guanzhong Plain urban agglomeration - Tonghui Yu; Xinyu Li; Jingbo Liang; Mengru Wang; Yu Zhang; Xufeng Cui (Environment, Development and Sustainability, 2026)

A supply-flow-demand network framework for unraveling the compounded impacts of future climate and functional space on urban water-soil ecosystem services - Yu Wang; Junfei Chen; Tonghui Ding; Yufei Han; Xiaodong Yan; Jiayuan Guo; Qingqing Ban; Ting Cheng (Sustainable Cities and Society, 2026)

Southern urban forest converted from orchard abandonment: a potentially important N2O source driven by warm-humid climate - Lifang Wu; Dingxi Chen; Zhongcong Sun; Zetong Niu; Bei Zhang; Tonghui Yang; Ao Wang; Zhixi Wu; Longfei Yu (Environmental Research, 2025)

Pressure-mediated band engineering and cation ordering for enhanced thermoelectric performance in CuInTe2 chalcopyrites - Jiaman Wei; Wei Yu; Zhijian Li; Jiaxin Hu; Tonghui Wang; Yuan Yu; Xin Guo (Chemical Engineering Journal, 2025)

Deciphering the spatial code of the Yellow River Basin: A novel framework for optimizing land use functions and zoning identification strategies - Tonghui Yu; Xuan Huang; Xi Chen; Jingbo Liang; Xinyu Li; Xufeng Cui (Journal of Environmental Management, 2025)

Deciphering the green-eco nexus: multi-dimensional analysis and policy pathways for the symbiotic advancement of green manufacturing and ecological resilience within Yangtze River Economic Belt - Tonghui Yu; Xinyu Li; Xuan Huang; Xufeng Cui (Environment, Development and Sustainability, 2025)

Seasonal variability of sea surface pCO2 and air-sea CO2 flux in a high turbidity coastal ocean in the vicinity of the East China Sea - Zhedong Yang; Xufeng Yang; Cai Zhang; Yimin Jin; Xupeng Hu; Xian Zhou; Tonghui Zhuang; Jianghao Ning; Jiangning Zeng; Peisong Yu (Frontiers in Marine Science, 2025)
The sea surface partial pressure of CO 2 ( p CO 2 ) and air-sea carbon flux in estuarine and bay areas, influenced by both natural and anthropogenic factors, remain poorly understood and inadequately assessed. This study, based on seasonal underway observations conducted in 2024, analyzed the seasonal variations in surface seawater p CO 2 and air-sea CO 2 flux in the high-turbidity coastal waters of Zhejiang, including Hangzhou Bay (HZB), Xiangshan Bay (XSB), Sanmen Bay (SMB), and the nearshore waters (NSW). The results indicate that the p CO 2 in the study area ranged from 194 to 739 μatm throughout the year, exhibiting significant spatiotemporal heterogeneity. In HZB, the lowest p CO 2 was observed in winter, averaging 453 μatm, whereas the values in spring and summer were around 600 μatm, with a subsequent decline to 481 μatm in autumn. In XSB, p CO 2 reached its minimum in winter (194 μatm), attributed to vigorous biological activity, and peaked in spring, averaging 639 μatm. In SMB, p CO 2 was relatively lower in autumn and winter (~470 μatm), and higher in spring and summer (~640 μatm). In the NSW, p CO 2 was lower in winter and spring (~445 μatm), and increased to ~510 μatm in summer and autumn. The p CO 2 was predominantly regulated by sea surface temperature and horizontal mixing, while other factors like biological activity also had significant impacts. The annual average CO 2 flux was 6.0±3.7 mmol m -2 d -1 in HZB, 1.2±2.3 mmol m -2 d -1 in XSB, 7.0±3.2 mmol m -2 d -1 in SMB and 5.2±5.9 mmol m -2 d -1 in the NSW. Higher wind speeds in autumn and winter, coupled with elevated the p CO 2 difference between the surface water and the atmosphere (Δ p CO 2 ) in spring and summer, collectively drove the seasonal variations in CO 2 flux. On an annual scale, both the estuarine and bay areas and the nearshore regions functioned as carbon sources.

Spatio-temporal evolution and drivers of coupling coordination between digital infrastructure and inclusive green growth: Evidence from the Yangtze River economic belt - Tonghui Yu; Yu Zhang; Shanshan Jia; Xufeng Cui (Journal of Environmental Management, 2025)

Phosphorus Removal and Recovery During Microalgae-Based Wastewater Treatment: A Mini-review - Dinghao Yu; Luming Yan; Jingqi Shi; Yang Liu; Aimin Zhang; Yabo Wang; Yongkui Zhang; Tonghui Xie (International Journal of Environmental Research, 2024)

A reduction-driven directed aggregation strategy for fabricating stretchable conductive core-sheath fibers in wearable electronics - Bin Yu; Qin Gu; Guangkai Hu; Tonghui Yang; Mengjiao Liu; Haiyan Shi; Zhengchen Xiang; Tao Huang; Meifang Zhu; Hao Yu (Chemical Engineering Journal, 2024)

A phytoexclusion strategy for reducing contamination risk of rice based on low-Cd natural variations pyramid of root transporters - Yan Huili; Liu Ruoxi; Peng Zhimei; Zhang Hezifan; Hao Shuangnan; Guo Hanyao; Wang Binghan; Wang Weiping; Yu Yijun; Zhang Hongliang; Qian Tonghui; Xu Wenxiu; et al. (Journal of Hazardous Materials, 2023)

Cross-modal aroma–taste interactions between lactone aroma and sourness and saltiness in solutions at concentrations relevant to Cheddar cheese - Chen Chen; Xiaocong Zhang; Zheng Liu; Tonghui Tian; Haiyan Yu; Haibin Yuan; Xinman Lou; Huaixiang Tian (International Dairy Journal, 2023)

Emergency risk assessment of sudden water pollution in South-to-North Water Diversion Project in China based on driving force–pressure–state–impact–response (DPSIR) model and variable fuzzy set - Xueyou Zhang; Junfei Chen; Chong Yu; Qian Wang; Tonghui Ding (Environment, Development and Sustainability, 2023)

Exploring the differences of ecosystem service values in different functional areas of metropolitan areas - Tonghui Ding; Junfei Chen; Zhou Fang; Yu Wang (Sustainable Production and Consumption, 2023)

Facile electrochemically induced vacancy modulation of NiCo2O4 cathode toward high-performance aqueous Zn-based battery - Yu Zhang; Dan Sun; Yixun Wang; Xiaoqi Liu; Hongman Sun; Tonghui Cai; Xuejin Li; Han Hu; Xiaoyun Zhang; Wei Xing; Zifeng Yan (Chemical Engineering Journal, 2023)

The Potential Roles of Aquaporin 4 in Alzheimer’s Disease - Yu-Long Lan; Jie Zhao; Tonghui Ma; Shao Li (Molecular Neurobiology, 2016)

Endothelin-1 Stimulates the Expression of L-Type Ca2+ Channels in Neonatal Rat Cardiomyocytes via the Extracellular Signal–Regulated Kinase 1/2 Pathway - Liangzhu Yu; Mincai Li; Tonghui She; Chunrong Shi; Wei Meng; Banghua Wang; Menglin Cheng (The Journal of Membrane Biology, 2013)

The spatio-temporal pattern of historical disturbances of an evergreen broadleaved forest in East China: a dendroecological analysis - Kun Song; Qian Yu; KanKan Shang; Tonghui Yang; LiangJun Da (Plant Ecology, 2011)